International coordinates of the right to protect human rights: the Mexican case - López Libreros, José Manuel (Revista Internacional & Comparada de Derechos Humanos, 2023)
This paper analyzes the human right to defend human rights, as an autonomous right of international source that has materialized in the Mexican legal system through jurisprudence, where it is recognized as part of the block and parameter of constitutional regularity. The study, essentially qualitative, deductive and documentary, focuses both on the analysis of the theoretical positions and relevant international instruments of the Universal and Inter-American Human Rights System, which give normative basis to the right under study, and on the impact and interaction of these international sources with the sources of the Mexican legal system in the recognition as an autonomous human right; the latter, through the review of the Amparo en Revisión 1031/2019, resolved by the First Chamber of the Supreme Court of Justice of the Nation.
Keywords: Human rights; human rights defenders; international human rights law; international human rights standards